2003
DOI: 10.1186/bcr754
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of mammary gland development reveals putative roles for death receptors and immune mediators in post-lactational regression

Abstract: IntroductionMammary gland development during the pregnancy cycle is characterized by successive phases of cell growth, differentiation, high metabolic activity and apoptosis. At the ultrastructural level this includes dramatic changes in tissue architecture, involving ductal epithelial branching and morphogenesis, invasion of tissue compartments, vascularization and subsequent organized remodelling. These events are highly reproducible and strictly controlled at the transcriptional level by circulating hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(184 citation statements)
references
References 74 publications
11
168
1
1
Order By: Relevance
“…In this process, the remaining MFGs are also cleared from the gland (8). The involution process is regulated at the transcriptional level and is associated with the up-or down-regulation of a set of genes (26,27). In this report, we showed that the MFG-E8 gene was strongly expressed in the mammary gland during the lactation and involution periods.…”
Section: Discussionmentioning
confidence: 57%
“…In this process, the remaining MFGs are also cleared from the gland (8). The involution process is regulated at the transcriptional level and is associated with the up-or down-regulation of a set of genes (26,27). In this report, we showed that the MFG-E8 gene was strongly expressed in the mammary gland during the lactation and involution periods.…”
Section: Discussionmentioning
confidence: 57%
“…Experimental animal models have been invaluable in mammary gland research (reviewed in Hennighausen and Robinson, 2001), enabling the identification of mammary stem (Smalley et al, 2005;Shackleton et al, 2006;Stingl et al, 2006); and luminal progenitor cells (Sleeman et al, 2006(Sleeman et al, , 2007Asselin-Labat et al, 2007) and the molecular changes that are associated with the different phases of post-pubertal mammary development (Master et al, 2002;Clarkson et al, 2004;Stein et al, 2004). Mouse models displaying defects in these processes have also been very useful, for example, Gata-3, Elf-5 and Stat5a knockout mice have helped define the cellular events involved in the development of luminal and secretory cells, respectively (Asselin-Labat et al, 2007;Oakes et al, 2008;Yamaji et al, 2009), whereas PrlR and Gal knockout mice have shed light on the molecular events associated with the secretory activation stage of lactation (Naylor et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic transcriptional profiling has been used recently to study the hairgrowth cycle and other cyclic processes, including the circadian rhythm and cycles in the female reproductive system such as mammary gland regulation (32)(33)(34)(35)(36)(37). We believe that our approach can be applied to time-course gene expression studies such as these to identify clusters of genes associated with a cyclic process of interest occurring in the context of a complex tissue.…”
Section: Genes Participating In Distinct Genetic Pathways Are Enrichementioning
confidence: 99%